Preparation method of scandium-aluminum-nitrogen thin film
By epitaxially growing the aluminum nitride base layer and the gallium nitride sacrificial layer on the substrate, and peeling the sacrificial layer after transfer between equipment, and growing the scandium aluminum nitrogen film layer on the aluminum nitride base layer, the problem of oxidation of the aluminum nitride base layer is solved and the crystal quality and performance of the film layer are improved.
Patent Information
- Application Number
- CN202411763731.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-03
AI Technical Summary
When preparing scandium aluminum nitrogen film, the aluminum nitride base layer is prone to oxidation during the transfer between different equipment, resulting in blurred interfaces and affecting the crystal quality and performance of scandium aluminum nitrogen film layer.
The aluminum nitride base layer and the gallium nitride sacrificial layer are epitaxially grown on the substrate, and the gallium nitride sacrificial layer is peeled off and the scandium aluminum nitrogen film layer is grown on the aluminum nitride base layer. In this way, oxidation of the aluminum nitride base layer during the transfer between equipment is avoided.
This method effectively improves the crystal quality of scandium aluminum nitrogen film layer, reduces acoustic transmission loss, and improves transmission efficiency. It is suitable for high-performance filter applications.
Smart Images

Figure CN119776990A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of semiconductor materials, and specifically relates to a method for preparing a scandium aluminum nitride thin film. Background Art
[0002] Aluminum nitride (AlN) material has the advantages of high acoustic wave transmission speed, good temperature stability and low dielectric loss, and is one of the ideal materials for the new generation of filters. Growing high-quality aluminum nitride film layers through epitaxial technology is the basis for preparing high-quality BAW filters, especially high-quality FBAR filters. Furthermore, by adding scandium (Sc) elements to AlN, the electromechanical coupling coefficient of the material can be effectively improved. At present, single-crystal ScAlN film is one of the development directions for preparing high-performance filter materials.
[0003] AlN single crystal thin film can be chemically synthesized by metal organic chemical vapor deposition (MOCVD) process, but there are stress problems in heterogeneous epitaxy, especially when preparing large size and / or thick film, the stress is more obvious, and it is very easy to have warping or cracking problems. When other processes such as physical vapor deposition (PVD) are used to prepare aluminum nitride film layer, the stress problem can be solved, but by replacing the Sc / Al alloy target to grow ScAlN film, it is easy to grow into a polycrystalline film, which reduces the performance of subsequent devices. The prior art proposes to grow a high-quality MO~AlN (aluminum nitride monolayer) seed layer by combining MOCVD with PVD, and then grow ScAlN on the seed layer by PVD, inheriting the crystal quality and surface of the bottom seed layer. This method can greatly improve the overall performance of AlN and maintain low in-plane stress. However, the growth method involves more than two devices, and the transfer between devices is required during the epitaxial process. The transfer process is very likely to cause dirt and surface oxidation. Summary of the invention
[0004] In view of this, the present application provides a method for preparing a scandium aluminum nitride (ScAlN) thin film, in which an aluminum nitride (AlN) base layer and a gallium nitride (GaN) sacrificial layer are epitaxially grown on a substrate in sequence, and then the gallium nitride sacrificial layer is peeled off to avoid oxidation of the aluminum nitride base layer during the transfer between different devices, so that a scandium aluminum nitride film layer can be grown on the aluminum nitride base layer through different epitaxial deposition processes, which is beneficial to improving the crystal quality of the scandium aluminum nitride film layer.
[0005] In a first aspect, the present application provides a method for preparing a scandium aluminum nitride thin film, the preparation method comprising the following steps: step 1, obtaining a base substrate and a functional composite layer obtained by epitaxial growth on the base substrate, the functional composite layer comprising an aluminum nitride base layer and a gallium nitride sacrificial layer; the aluminum nitride base layer is in contact with the base substrate, and the gallium nitride sacrificial layer is arranged on a side surface of the aluminum nitride base layer away from the base substrate; step 2, peeling off the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer; step 3, growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template. The present application epitaxially grows an aluminum nitride base layer on a base substrate, and the high-quality aluminum nitride base layer can be used as a seed crystal to lay the foundation for the subsequent epitaxial growth of a scandium aluminum nitride film layer with high crystal quality; in addition, the present application grows a gallium nitride (GaN) sacrificial layer on the surface of the aluminum nitride base layer facing away from the base substrate as a protective layer for the aluminum nitride base layer, so as to prevent the aluminum nitride base layer from being exposed to the atmosphere during the transfer between different process equipment and reacting with free oxygen molecules to cause oxidation. After the gallium nitride sacrificial layer is peeled off, the growth and quality of the subsequent scandium aluminum nitride film layer are not affected. The present application can use a variety of epitaxial growth processes to avoid the stress problem of heterogeneous epitaxy using a single MOCVD process. By adjusting the conditions of the epitaxial process, it is beneficial to improve the crystal quality and piezoelectric constant of the scandium aluminum nitride film. When used in filters, it has the advantages of low acoustic transmission loss and high efficiency.
[0006] Preferably, the growth conditions of the aluminum nitride substrate layer include: a temperature of 1100-1300°C, a pressure of 30-200 Torr, a gas volume flow rate of the aluminum source of 10-30 sccm, and a gas volume flow rate of ammonia of 10-20 slm. The present application adopts a metal organic chemical vapor deposition process (MOCVD) to prepare the aluminum nitride substrate layer. By controlling the process conditions, a single crystal aluminum nitride substrate layer can be obtained, providing conditions for the subsequent growth of a high-quality scandium aluminum nitride film layer.
[0007] Preferably, the root mean square roughness (RMS) of the aluminum nitride substrate layer is in the range of 0.5≤Rq≤0.8nm. The present application controls the aluminum nitride substrate layer to have a relatively low roughness, which is beneficial to improving the growth quality of the subsequent scandium aluminum nitride film layer; in addition, a thinner gallium nitride sacrificial layer is used on the aluminum nitride substrate layer with relatively low roughness to ensure complete coverage of the aluminum nitride substrate layer, thereby avoiding oxidation and contamination of the aluminum nitride substrate layer during transfer between devices.
[0008] Preferably, the half-width (FWHM) of the (002) peak of the aluminum nitride substrate layer is in the range of 0.2°≤FWHM≤0.6°. By controlling the half-width (FWHM) of the (002) peak of the aluminum nitride substrate layer, the c-axis lattice order of the aluminum nitride substrate layer is ensured, and a single-crystal aluminum nitride substrate layer is formed, which is beneficial to reducing crystal defects and improving the growth quality of the subsequent scandium aluminum nitride film layer.
[0009] Preferably, the aluminum nitride base layer has a thickness of 50-100 nm.
[0010] Preferably, the growth conditions of the gallium nitride sacrificial layer include: a temperature of 800-900°C, a pressure of 50-70 Torr, a gas volume flow rate of 300-380 sccm of the gallium source, and a gas volume flow rate of 40-60 slm of the nitrogen source. The gallium nitride sacrificial layer is arranged on the aluminum nitride base layer, and the aluminum nitride base layer is completely isolated from the atmospheric environment by fully covering the aluminum nitride base layer, thereby avoiding oxidation and contamination problems caused by the epitaxial wafer during the transfer between devices.
[0011] Preferably, the gallium nitride sacrificial layer includes 1 to 10 gallium nitride monolayers. In the present application, the gallium nitride sacrificial layer is composed of gallium nitride monolayers. By limiting the thickness of the gallium nitride layer to 1 to 10 monolayers, it is ensured that the GaN sacrificial layer can completely cover the aluminum nitride base layer to avoid oxidation caused by uncovered local areas, and also avoid the problem of incomplete desorption of the GaN sacrificial layer during subsequent baking due to excessive thickness.
[0012] Preferably, the gallium nitride layer includes 3 to 5 gallium nitride monolayers, and more preferably includes 4 gallium nitride monolayers.
[0013] Preferably, the step 2 of stripping the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer includes: baking the functional composite layer to strip the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer; introducing argon gas during the baking process, and the flow rate of the argon gas is 20-50 sccm; the temperature of the baking process is 500-900°C, the time of the baking process is 2-30 minutes, and the baking pressure is 2-4 mTorr. The baking process is used to desorb the gallium nitride sacrificial layer from the aluminum nitride base layer and expose the complete aluminum nitride surface, so as to achieve complete stripping of the sacrificial layer in the vacuum chamber. At the same time, the baking process is conducive to removing impurities such as water and oxygen accumulated on the surface of the epitaxial wafer, ensuring that the surface of the epitaxial wafer is clean, which is conducive to the subsequent preparation of high-quality scandium aluminum nitride film layers, and can also preheat the aluminum nitride base layer, which is conducive to improving the preparation efficiency of the subsequent scandium aluminum nitride film layers. During the baking process, argon (Ar) is introduced and the argon flow rate is regulated, so that argon can be used as a protective gas to inhibit the reaction between aluminum nitride and residual water and oxygen in the cavity after high-temperature desorption of gallium nitride while ensuring the stability of the pressure in the cavity. The combination of sacrificial layer coverage and intracavity desorption technology in this application can well achieve complete isolation of the epitaxial wafer from the atmosphere. At the same time, the growth and desorption of the sacrificial layer are directly carried out in situ through the MOCVD and PVD systems, and the process is simple and efficient.
[0014] Preferably, the flow rate of the argon gas is 25-35 sccm; the temperature of the baking treatment is 600-800° C., and the time of the baking treatment is 10-15 min. For example, the baking treatment is baking at 650° C. for 10 min.
[0015] Preferably, the baking process further comprises: the pressure of the baking process is 2-4 mTorr. By controlling the baking process to be performed at a relatively low pressure, it is beneficial for the escape and removal of the gallium nitride sacrificial layer.
[0016] Preferably, the growth conditions of the scandium aluminum nitride film layer include: the sputtering target is a scandium aluminum alloy target, the sputtering power is 1500-3000W, the substrate temperature is 500-800°C, the gas volume flow rate of the nitrogen source is 100-200sccm, the gas volume flow rate of the argon source is 20-50sccm, and the working pressure is 2-6mTorr. The present application adopts a physical vapor deposition (PVD) process for the epitaxial growth of the scandium aluminum nitride film layer. By controlling the growth process of the scandium aluminum nitride film layer, it is beneficial to modulate the stress problems caused by lattice mismatch and thermal mismatch in the scandium aluminum nitride heteroepitaxial growth, and a scandium aluminum nitride film with a relatively high thickness can be obtained. At the same time, it is ensured that the scandium aluminum nitride film has a low residual stress, which can avoid cracks and also avoid the influence of subsequent chip processes due to excessive warping.
[0017] Preferably, the scandium aluminum nitride film layer has a thickness of 200 to 1000 nm.
[0018] Based on the preparation method of the scandium aluminum nitride film of the present application, an aluminum nitride base layer is used as the growth basis of the scandium aluminum nitride film layer, providing conditions for growing a high-quality scandium aluminum nitride film layer. Subsequently, the scandium aluminum nitride film layer can be grown by a process different from that of the aluminum nitride base layer, such as a physical vapor deposition method, thereby avoiding the stress problem caused by lattice mismatch and thermal mismatch in the process of single-crystal aluminum nitride heteroepitaxial growth using only the MOCVD process. By setting a gallium nitride sacrificial layer, the aluminum nitride base layer is isolated from contact with air during the transfer process between different process equipment, thereby avoiding the oxidation problem of the aluminum nitride base layer. In addition, the aluminum nitride sacrificial layer can be removed by baking in the scandium aluminum nitride film preparation equipment, which will not affect the crystal quality of the aluminum nitride base layer, thereby helping to improve the crystal quality of the scandium aluminum nitride film layer subsequently grown on the aluminum nitride base layer. The scandium aluminum nitride thin film prepared by the method of the present application includes an aluminum nitride base layer and a scandium aluminum nitride film layer. The scandium aluminum nitride film layer can obtain a scandium aluminum nitride thin film that is close to a single crystal by nucleation and crystallization on a high-quality aluminum nitride base layer, thereby ensuring high crystal quality and piezoelectric constant, reducing acoustic transmission loss, and improving transmission efficiency, which is conducive to application in high-performance filters. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a flow chart of a method for preparing a scandium aluminum nitride thin film according to a specific embodiment of the present application;
[0020] Figure 2 These are the XRD diffraction analysis results of the scandium aluminum nitride films prepared in Example 1, Example 4 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] In the prior art, the metal organic chemical vapor deposition (MOCVD) process can be used to prepare AlN single crystal thin films (hereinafter referred to as MO-AlN) with high crystal quality, but it is difficult to overcome the stress problem caused by heteroepitaxial growth. The prior art proposes a process that combines metal organic chemical vapor deposition with physical vapor deposition (PVD), which realizes the preparation of near-single crystal scandium aluminum nitride film layers, and the crystal quality is improved to a certain extent, but it still cannot meet the performance requirements of high-frequency broadband filters for materials, and the overall process needs to be further optimized.
[0023] The inventors of the present application discovered during the preparation of the scandium aluminum nitride film that the scandium aluminum nitride film is easily oxidized when in contact with air during the extracavity transfer process between different processes. After the aluminum nitride film used as the growth template is oxidized, an Al-NO mixed bond region is formed at the interface, making the interface blurred and unclear. The scandium aluminum nitride layer is difficult to effectively inherit the (002) lattice orientation of the underlying MO-AlN, causing the overall (002) peak half-width (FWHM) of the scandium aluminum nitride film prepared by physical vapor deposition (hereinafter referred to as PVD-ScAlN) to decrease, indicating that the crystal quality and C-axis order of PVD-ScAlN are reduced, which will seriously hinder the acoustic transmission of the thick FBAR filter device, reduce the Q factor of the device, and increase the insertion loss of the device, thereby seriously affecting the working performance of the device. At the same time, after the O at the interface replaces the N bond, it can affect the lattice structure of the PVD-ScAlN, causing the polarity reversal of the PVD-ScAlN in the local area, reducing the electromechanical coupling coefficient (K t 2 ), which seriously affects the bandwidth of subsequent devices.
[0024] In view of this, the present application provides a method for preparing a scandium aluminum nitride thin film, the preparation method comprising the following steps: step 1, obtaining a base substrate and a functional composite layer obtained by epitaxial growth on the base substrate, the functional composite layer comprising an aluminum nitride base layer and a gallium nitride sacrificial layer; the aluminum nitride base layer is in contact with the base substrate, and the gallium nitride sacrificial layer is arranged on a side surface of the aluminum nitride base layer away from the base substrate; step 2, peeling off the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer; step 3, growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template.
[0025] In some embodiments, the present application can use a single crystal AlN thin film material prepared by the MOCVD process as a seed crystal, and use PVD and other processes on the seed crystal template to perform nucleation crystal growth, so as to obtain a scandium aluminum nitride thin film close to a single crystal. The gallium nitride sacrificial layer prevents oxidation problems from occurring when the seed crystal template is transferred between different process equipment, thereby ensuring the quality of the seed crystal template, thereby facilitating the control of the single crystal growth of the scandium aluminum nitride film layer during the nucleation crystal growth process, and the crystal quality is high.
[0026] Figure 1 A flow chart showing a method for preparing a scandium aluminum nitride thin film according to some specific embodiments of the present application is shown in FIG. Figure 1As shown, the present application first uses the MOCVD process to epitaxially grow an aluminum nitride base layer on a substrate (base substrate), and then in-situ grows a gallium nitride sacrificial layer on the aluminum nitride base layer. The gallium nitride sacrificial layer is used as an anti-oxidation protective layer for the aluminum nitride base layer, and then the substrate epitaxially grown with the gallium nitride sacrificial layer and the aluminum nitride base layer is transferred between devices, from the MOCVD device to the PVD device. After that, the substrate epitaxially grown with the gallium nitride sacrificial layer and the aluminum nitride base layer is baked in the PVD device, and the gallium nitride sacrificial layer is peeled off from the surface of the aluminum nitride base layer under high temperature and low pressure conditions, so that the gallium nitride sacrificial layer is desorbed to obtain a template containing only the base substrate and the aluminum nitride base layer, and finally the scandium aluminum nitrogen functional layer is in-situ grown on the aluminum nitride base layer using the PVD process.
[0027] Optionally, the base substrate may be made of conventional semiconductor single crystal materials in the art, for example, the base substrate may be selected from any one of silicon, sapphire, and silicon carbide.
[0028] In some embodiments, the aluminum nitride base layer may be grown by a metal organic chemical vapor deposition (MOCVD) process; and the scandium aluminum nitride film layer may be grown by a physical vapor deposition (PVD) process.
[0029] In some embodiments, the gallium nitride sacrificial layer includes 1 to 10 gallium nitride monolayers. In the present application, the gallium nitride monolayer refers to a monolayer formed by orderly arrangement of gallium nitride molecules on a deposition surface, which can be grown and prepared by MOCVD process.
[0030] Optionally, to avoid oxidation of the aluminum nitride base layer, after the aluminum nitride base layer is grown, a gallium nitride sacrificial layer is grown in situ on the aluminum nitride base layer using a MOCVD process; after the gallium nitride sacrificial layer is grown, the functional composite layer is transferred to a PVD device, and a baking process is performed to peel off the gallium nitride sacrificial layer, and then the scandium aluminum nitride film layer is grown in situ. In this application, the in-situ growth of the gallium nitride sacrificial layer means that after the growth of aluminum nitride is completed, there is no need to replace the growth equipment, only change the input source, and continue to grow in the same equipment; the in-situ growth of the scandium aluminum nitride film layer means that it is grown in the original equipment without moving the base substrate and the aluminum nitride base layer.
[0031] Example
[0032] The technical solution of the present application is described below in conjunction with specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from common commercially available products, and the devices or equipment used are all purchased from conventional market sales channels.
[0033] Example 1
[0034] The method for preparing the scandium aluminum nitride thin film of this embodiment comprises the following steps:
[0035] Step 1: Use a silicon wafer as a base substrate, and epitaxially grow a functional composite layer on the base substrate. The functional composite layer includes an aluminum nitride base layer and a gallium nitride sacrificial layer epitaxially grown on the silicon wafer in sequence. The aluminum nitride base layer is grown on the surface of the base substrate using an MOCVD process, and the growth conditions include: a temperature of 1100°C, a pressure of 100Torr, a gas volume flow rate of 10sccm for the aluminum source, and a gas volume flow rate of 10slm for the nitrogen source. The prepared aluminum nitride base layer has a root mean square roughness Rq of 0.8nm and a (002) peak half-height width FWHM of 0.4°.
[0036] The gallium nitride sacrificial layer is grown in situ on the surface of the aluminum nitride base layer away from the base substrate by MOCVD process, and the growth conditions include: temperature of 850°C, pressure of 70 Torr, gas volume flow rate of gallium source of 300 sccm, and gas volume flow rate of nitrogen source of 40 slm. The prepared gallium nitride sacrificial layer includes 4 gallium nitride monolayers.
[0037] Step 2: Remove the functional composite layer from the MOCVD device and place it in the PVD device. Then bake the functional composite layer to peel off the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer. The baking conditions include: introducing argon gas during the baking process, the argon gas flow rate is 20sccm, the temperature is 650°C, the time is 10min, and the pressure is 2mTorr.
[0038] Step 3, growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template, the growth conditions of the scandium aluminum nitride film layer include: the sputtering target is a scandium aluminum alloy target, the sputtering power is 2000 W, the substrate temperature is 500°C, the gas volume flow rate of the nitrogen source is 100 sccm, the gas volume flow rate of the argon source is 20 sccm, the working gas pressure is 2 mTorr, and the thickness of the obtained scandium aluminum nitride film layer is 200 nm.
[0039] Example 2
[0040] The method for preparing the scandium aluminum nitride film of this embodiment comprises the following steps:
[0041] Step 1: Use a silicon wafer as a base substrate, and epitaxially grow a functional composite layer on the base substrate. The functional composite layer includes an aluminum nitride base layer and a gallium nitride sacrificial layer epitaxially grown on the silicon wafer in sequence. The aluminum nitride base layer is grown on the surface of the base substrate using an MOCVD process, and the growth conditions include: a temperature of 1200°C, a pressure of 30 Torr, a gas volume flow rate of 20 sccm for the aluminum source, and a gas volume flow rate of 15 slm for the nitrogen source. The prepared aluminum nitride base layer has a root mean square roughness Rq of 0.5 nm and a (002) peak half-height width FWHM of 0.2°.
[0042] The gallium nitride sacrificial layer is grown in situ on the surface of the aluminum nitride base layer away from the base substrate by MOCVD process, and the growth conditions include: temperature of 850°C, pressure of 50 Torr, gas volume flow rate of gallium source of 380 sccm, and gas volume flow rate of nitrogen source of 50 slm. The prepared gallium nitride sacrificial layer includes 10 gallium nitride monolayers.
[0043] Step 2: Remove the functional composite layer from the MOCVD device and place it in the PVD device. Then bake the functional composite layer to peel off the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer. The baking conditions include: introducing argon gas during the baking process, the argon gas flow rate is 20sccm, the temperature is 1200°C, the time is 2min, and the pressure is 3mTorr.
[0044] Step 3, growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template, the growth conditions of the scandium aluminum nitride film layer include: the sputtering target is a scandium aluminum alloy target, the sputtering power is 2500 W, the substrate temperature is 650°C, the gas volume flow rate of the nitrogen source is 150 sccm, the gas volume flow rate of the argon source is 40 sccm, the working gas pressure is 4 mTorr, and the thickness of the obtained scandium aluminum nitride film layer is 600 nm.
[0045] Example 3
[0046] The method for preparing the scandium aluminum nitride thin film of this embodiment comprises the following steps:
[0047] Step 1: Use a silicon wafer as a base substrate, and epitaxially grow a functional composite layer on the base substrate. The functional composite layer includes an aluminum nitride base layer and a gallium nitride sacrificial layer epitaxially grown on the silicon wafer in sequence. The aluminum nitride base layer is grown on the surface of the base substrate using an MOCVD process, and the growth conditions include: a temperature of 1300°C, a pressure of 200Torr, a gas volume flow rate of 30sccm for the aluminum source, and a gas volume flow rate of 20slm for the nitrogen source. The prepared aluminum nitride base layer has a root mean square roughness Rq of 0.8nm and a (002) peak half-height width FWHM of 0.4°.
[0048] The gallium nitride sacrificial layer is grown in situ on the surface of the aluminum nitride base layer away from the base substrate by MOCVD process, and the growth conditions include: temperature of 900°C, pressure of 60 Torr, gas volume flow rate of gallium source of 340 sccm, and gas volume flow rate of nitrogen source of 60 slm. The prepared gallium nitride sacrificial layer includes 5 gallium nitride monolayers.
[0049] Step 2: Remove the functional composite layer from the MOCVD device and place it in the PVD device. Then bake the functional composite layer to peel off the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer. The baking conditions include: introducing argon gas during the baking process, the argon gas flow rate is 20sccm, the temperature is 500°C, the time is 30min, and the pressure is 4mTorr.
[0050] Step 3, growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template, the growth conditions of the scandium aluminum nitride film layer include: the sputtering target is a scandium aluminum alloy target, the sputtering power is 3000 W, the substrate temperature is 800°C, the gas volume flow rate of the nitrogen source is 200 sccm, the gas volume flow rate of the argon source is 50 sccm, the working gas pressure is 6 mTorr, and the thickness of the obtained scandium aluminum nitride film layer is 1000 nm.
[0051] Example 4
[0052] The method for preparing the scandium aluminum nitride thin film of this embodiment is different from that of Embodiment 1 only in that the gallium nitride sacrificial layer prepared in step 1 includes 20 gallium nitride monolayers.
[0053] Example 5
[0054] The method for preparing the scandium aluminum nitride thin film of this embodiment is different from that of Embodiment 1 only in that the root mean square roughness Rq of the aluminum nitride base layer is 1.5 nm.
[0055] Comparative Example 1
[0056] The preparation method of the scandium aluminum nitride film in this comparative example is different from that in Example 1 only in that the gallium nitride sacrificial layer and the baking treatment are omitted, and the aluminum nitride base layer prepared in step 1 is directly transferred to the PVD equipment for the subsequent step 3 of preparing the scandium aluminum nitride film layer.
[0057] Comparative Example 2
[0058] The method for preparing the scandium aluminum nitride film of this embodiment is different from that of embodiment 1 only in that the baking treatment step is omitted, and in step 2, after the functional composite layer is placed in the PVD equipment, the scandium aluminum nitride film layer is directly grown on the gallium nitride sacrificial layer.
[0059] Test Example 1
[0060] The scandium aluminum nitride thin films prepared by the preparation methods of Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to X-ray diffraction analysis (XRD) to measure the half-maximum width (FWHM) of the (002) peak of each scandium aluminum nitride thin film. The XRD diffraction analysis results of the scandium aluminum nitride thin films prepared by Example 1, Example 4 and Comparative Examples 1 to 2 are as follows: Figure 2As shown; the piezoelectric constant (D33 value) of the scandium aluminum nitride film prepared by the method of Example 1 and Comparative Example 1 was tested using a quasi-static D33 tester, and the results are shown in Table 1 below.
[0061] Table 1
[0062] serial number (002)FWHM(") Piezoelectric constant (pC / N) Example 1 553 5.2 Example 2 573 4.3 Example 3 610 4.1 Example 4 760 4.0 Example 5 858 4.0 Comparative Example 1 1127 1.9 Comparative Example 2 1334 2.1
[0063] As can be seen from Table 1, the half-width of the (002) peak of the scandium aluminum nitride film prepared in Example 1 is 553" (" is in units: arc seconds, 1" = 1 / 3600°). In comparison, after omitting the gallium nitride sacrificial layer and baking process, the half-width of the (002) peak of the scandium aluminum nitride film prepared in Comparative Example 1 is 1127". The gallium nitride sacrificial layer and baking process in the present application can greatly reduce the half-width of the (002) peak of the scandium aluminum nitride film and improve the crystal quality of the scandium aluminum nitride film. At the same time, its D33 test results also show that the piezoelectric constant of Example 1 is significantly greater than that of Comparative Example 1, and is close to the piezoelectric constant of single crystal scandium aluminum nitride, indicating that the scandium aluminum nitride film of Example 1 has better c-axis order, and compared with Comparative Example 1, it greatly suppresses the generation of polarity reversal, thereby avoiding the piezoelectric polarization cancellation caused by polarity reversal. This proves that the gallium nitride sacrificial layer and baking treatment of the present application have the advantage of improving the crystal quality of the scandium aluminum nitride film, thereby being beneficial to improving the dielectric properties of the scandium aluminum nitride film and promoting its application in high-frequency broadband filters.
[0064] Compared with Example 1 and Comparative Example 2, if the gallium nitride baking is not performed, the entire gallium nitride layer will remain on the aluminum nitride base layer, becoming an insertion layer between the aluminum nitride base layer and the scandium aluminum nitride film layer. The strong coupling between the insertion layer and the aluminum nitride base layer and the film layer will bring about a more complex stress situation, and the insertion of gallium nitride will cause lattice mismatch between the interfaces, which will seriously affect the crystal quality of aluminum nitride.
[0065] Comparing Example 1 with Example 4, the half-height width of the (002) peak of the scandium aluminum nitride film prepared by using an overly thick gallium nitride sacrificial layer in Example 4 is 760", and the crystal quality of the scandium aluminum nitride film is reduced. This is because the overly thick gallium nitride sacrificial layer will cause the gallium nitride sacrificial layer to be incompletely removed during the subsequent baking process, resulting in part of the gallium nitride still being retained on the aluminum nitride substrate layer, resulting in a mixed structure of gallium nitride and aluminum nitride in the local area, thereby reducing the crystal quality of the scandium aluminum nitride film layer to a certain extent. The present application controls the thickness of the gallium nitride sacrificial layer to be 1 to 10 gallium nitride monolayers, thereby protecting the aluminum nitride substrate layer from oxidation while ensuring the removal effect of the subsequent baking process, thereby improving the crystal quality of the subsequent scandium aluminum nitride film layer.
[0066] Example 5 Based on Example 1, the root mean square roughness of the aluminum nitride substrate layer is increased to 1.5nm, the half-height width of the (002) peak of the prepared scandium aluminum nitride film is 858", and the crystal quality has also decreased to a certain extent. The reason may be that the higher surface roughness will prevent the gallium nitride sacrificial layer from completely covering the aluminum nitride substrate layer. Therefore, the aluminum nitride substrate layer is at risk of being oxidized during the transfer process between devices, and the oxidation will affect the crystal quality of the subsequent growth of the scandium aluminum nitride film layer. The present application controls the root mean square roughness of the aluminum nitride substrate layer to be between 0.5 and 0.8nm, which is conducive to reducing or avoiding the oxidation risk of the aluminum nitride substrate layer, thereby ensuring the crystal quality of the scandium aluminum nitride film.
[0067] Examples 2 and 3 have similar crystal quality and surface roughness. Combining Examples 1-3, it can be seen that under the process conditions of this application, the gallium nitride sacrificial layer + baking process can very effectively optimize the crystal quality and piezoelectric coefficient of scandium aluminum nitride, and the process steps can be directly designed and operated in situ in the equipment without the need for external equipment. The process steps are simple and easy to operate. While greatly optimizing the crystal quality and piezoelectric performance of scandium aluminum nitride, the efficiency of the overall process is guaranteed.
[0068] Test Example 2
[0069] Auger electron spectroscopy (AES) was used to test the oxygen content of the scandium aluminum nitride thin films prepared in Example 1 and Comparative Example 1 to determine the oxidation degree of each scandium aluminum nitride thin film sample. The AES results showed that no oxygen content was detected at the interface of Example 1, while the oxygen content detected at the interface of Comparative Example 1 was 1×10 -16 It can be seen that the present application, by setting a gallium nitride sacrificial layer and baking treatment, is beneficial to protecting the aluminum nitride base layer and reducing the oxidation risk of the gallium nitride base layer when it is transferred between devices, thereby avoiding the oxidation problem of the aluminum nitride base layer and improving the crystal quality of the scandium aluminum nitride film.
[0070] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a scandium aluminum nitride thin film, characterized in that: The preparation method comprises the following steps: Step 1: obtaining a base substrate and a functional composite layer obtained by epitaxial growth on the base substrate, wherein the functional composite layer comprises an aluminum nitride base layer and a gallium nitride sacrificial layer; The aluminum nitride base layer is in contact with the base substrate, and the gallium nitride sacrificial layer is arranged on a surface of the aluminum nitride base layer facing away from the base substrate; Step 2, peeling the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer to obtain a template containing a base substrate and an aluminum nitride base layer; Step 3: growing a scandium aluminum nitride film layer on the aluminum nitride base layer of the template.
2. The preparation method according to claim 1, characterized in that: The growth conditions of the aluminum nitride base layer include: a temperature of 1100-1300° C., a pressure of 30-200 Torr, a gas volume flow rate of the aluminum source of 10-30 sccm, and a gas volume flow rate of the ammonia gas of 10-20 slm.
3. The preparation method according to claim 1, characterized in that: The root mean square roughness Rq of the aluminum nitride substrate layer is in the range of 0.5≤Rq≤0.8nm; and / or, The value range of the half-width (FWHM) of the (002) peak of the aluminum nitride substrate is 0.2°≤FWHM≤0.6°; and / or, The thickness of the aluminum nitride base layer is 50-100 nm.
4. The preparation method according to claim 1, characterized in that: The growth conditions of the gallium nitride sacrificial layer include: a temperature of 800-900° C., a pressure of 50-70 Torr, a gas volume flow rate of a gallium source of 300-380 sccm, and a gas volume flow rate of a nitrogen source of 40-60 slm.
5. The preparation method according to claim 1, characterized in that: The gallium nitride sacrificial layer includes 1 to 10 gallium nitride monomolecular layers.
6. The preparation method according to claim 5, characterized in that: The gallium nitride layer includes 3 to 5 gallium nitride monomolecular layers.
7. The preparation method according to claim 1, characterized in that: The step 2 of peeling the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer comprises: baking the functional composite layer to peel the gallium nitride sacrificial layer from the surface of the aluminum nitride base layer; During the baking process, argon gas is introduced, and the flow rate of the argon gas is 20-50 sccm; the temperature of the baking process is 500-900° C., and the time of the baking process is 2-30 minutes.
8. The preparation method according to claim 7, characterized in that: The flow rate of the argon gas is 25 to 35 sccm; the temperature of the baking treatment is 600 to 800° C., and the time of the baking treatment is 10 to 15 minutes; and / or, The baking process also includes: a pressure of the baking process is 2 to 4 mTorr.
9. The preparation method according to claim 1, characterized in that: The growth conditions of the scandium aluminum nitride film layer include: the sputtering target is a scandium aluminum alloy target, the sputtering power is 1500-3000W, the substrate temperature is 500-800°C, the gas volume flow rate of the nitrogen source is 100-200sccm, the gas volume flow rate of the argon source is 20-50sccm, and the working gas pressure is 2-6mTorr.
10. The preparation method according to claim 9, characterized in that: The thickness of the scandium aluminum nitride film layer is 200-1000nm.
Citation Information
Patent Citations
Silicon carbide-based AlScN template for high-frequency high-performance SAW device and preparation method of silicon carbide-based AlScN template
CN113871289A
Preparation method of piezoelectric film template for acoustic wave device
CN114362703A
Method for transferring gallium oxide epitaxial film on substrate
CN117253776A
Method for manufacturing piezoelectric thin film and device using same thin film
WO2021225426A1